2017
DOI: 10.7759/cureus.1674
|View full text |Cite
|
Sign up to set email alerts
|

Intensity Modulated Proton Therapy with Advanced Planning Techniques in a Challenging Hepatocellular Carcinoma Patient

Abstract: The use of radiation therapy has been increasing over recent years for the treatment of hepatocellular carcinoma (HCC). Proton beam therapy (PBT) has emerged as a promising treatment option for HCC patients due to its dosimetric advantages of sparing more normal liver tissue from radiation at low to moderate doses compared to photon-based treatments while still delivering high doses of radiation to tumors. The PBT therapy may be particularly beneficial in high-risk HCC cirrhotic patients with large, bulky tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The University of Washington group has also published a number of planning studies looking at avoidance of high functioning liver using both proton and VMAT photon plans. 58, 59 Most recently, they have published a series on 87 patients treated with liver SBRT using functional optimization with 99m Tc-sulfur colloid SPECT-CT in which no grade 3 and above toxicity was seen while maintaining excellent local control. 51 Building on these promising results, they currently have a trial open evaluating the role of SPECT-CT for radiation therapy and surgical planning for primary and metastatic liver cancers (NCT02881554).…”
Section: Functional Liver Imaging and Incorporation Into Radiation Plmentioning
confidence: 99%
“…The University of Washington group has also published a number of planning studies looking at avoidance of high functioning liver using both proton and VMAT photon plans. 58, 59 Most recently, they have published a series on 87 patients treated with liver SBRT using functional optimization with 99m Tc-sulfur colloid SPECT-CT in which no grade 3 and above toxicity was seen while maintaining excellent local control. 51 Building on these promising results, they currently have a trial open evaluating the role of SPECT-CT for radiation therapy and surgical planning for primary and metastatic liver cancers (NCT02881554).…”
Section: Functional Liver Imaging and Incorporation Into Radiation Plmentioning
confidence: 99%
“…Utilizing PBS-IMPT, a simultaneous integrated boost (SIB) and protection (SIP) technique may be more feasible than with photon-based IMRT and allow for dose escalation to the part of the tumor with lower-dose levels near critical OARs. 78 , 88 Kim et al reported results of a PBT-IMPT SIB approach in patients with advanced HCC with tumor vascular thrombosis (TVT): 2-yr local progression-free survival of 88%, OS of 51%, and no grade ≥3 toxicity. 78 Higher biologic equivalent dose was associated with better TVT response, which was an independent prognostic factor for improved OS.…”
Section: Proton Beam Therapy (Pbt) For Hccmentioning
confidence: 99%
“…This is equivalent to the use of respiratory gating/breath hold for PBT. However, the nature of PBT using pencil beam scanning techniques could require a significant number of breath holds which may be difficult for patients to comply as discussed by Apisarnthanarax et al (2017) [20]. Therefore, it may be more practical for some patients to be treated under free breathing conditions, so that the PBT is planned using the ITV.…”
Section: Methodsmentioning
confidence: 99%